Plant Growth and Tuber Yield of Several Exotic Potato Genotypes - Islam, M. T.; Hossain, M. M.; Rana, M.A.R.; Rahman, M.M. (Department of Agronomy and Horticulture, IPB University, 2020)
Potato stolon and tuber number are the most important determinants of yield and these traits are associated with planting time and genotype. This study was conducted to evaluate plant growth, tuber yield contributing traits and tuber yield of potato genotypes in two planting dates. The experiment was done in randomized complete block design with three replications. Results showed that plant growth and traits that contribute to tuber yield of potato were significantly influenced by planting dates and genotypes. Stolon and tuber number as well as tuber weight were periodically investigated. It was observed that the performance of those traits were always higher in 23rd November planting. Different genotypes performed differently on all the studied parameters. Among the genotypes tested, G1 (AC 10069) produced the highest number of stolons, tubers, tuber weight, length and yield of tuber as compared to the check variety. It was observed that 23rd November planted G1 (AC 10069) gave the highest tuber yield (17.79 t.ha-1) which was statistically similar with G3 (AC 10110) (17.00 t.ha-1) when compared to the check variety. It can be concluded that planting time as well as genotype are the critical factors that determine potato yield.